Effects Of Radio Transmitter Burdening On Locomotor Ability And Survival Of Iguana Hatchlings - Knapp, Charles (2009)
We performed a two-part experiment in 2007 and 2008 to investigate the effects of externally affixed radio transmitters on the locomotor performance and survival of green iguana {Iguana iguana) hatchlings. Using sprint and climb speeds as locomotor performance variables, we tested in the laboratory the initial speed, maximum burst speed, and overall speed of iguana hatchlings affixed with radio transmitters of 2.5, 5.0, 7.5, 10.0, and 15.0% transmitter-to-body-mass (BM) ratios. We then released iguana hatchlings into a Costa Rican lowland forest to record the survival of free-ranging iguanas affixed with transmitters of 5.0, 7.5, and 10.0% transmitter to BM ratios. Sprint speeds were not reduced significantly with transmitters of up to 15.0% body mass. Climb speeds, however, were reduced for two of three performance variables at the 10% BM ratio. We found no differences in survival probabilities between telemetered treatment groups released into the forest. The probability of survival over two field seasons for telemetered iguanas ranged from 52.2 65.2% over a 24-30 day assessment period. For telemetered iguanas, percentage BM growth was significantly less for animals affixed with 10.0% BM transmitters than for control iguanas without transmitters. We suggest transmitter-to-body-mass ratios for cryptic arboreal lizard species should not exceed 7.5% based on lower climb performance in the laboratory and lower relative mass gain for free-ranging iguanas with >10.0% BM transmitters. Because lizard life histories vary substantially, researchers should be proactive in evaluating the energetic expenditures, foraging strategies, and escape responses of focal species to minimize effects of transmitter and attachment techniques.